Teaching outside the box : how to grab your students by their brains - Johnson, LouAnne (Jossey-Bass, 2011)
"The handbook for improving morale by managing, disciplining and motivating your students This second edition of the bestselling book includes practical suggestions for arranging your classroom, talking to students, avoiding the misbehavior cycle, and making your school a place where students learn and teachers teach. The book also contains enlivening Q&A from teachers, letters from students, and tips for grading. This new edition has been expanded to include coverage of the following topics: discipline, portfolio assessments, and technology in the classroom. Includes engaging questions for reflection at the end of each chapter. Johnson is the author of The New York Times bestseller Dangerous Minds (originally My Posse Don't Do Homework). Contains a wealth of practical tools that support stellar classroom instruction This thoroughly revised and updated edition contains comprehensive advice for both new and experienced teachers on classroom management, discipline, motivation, and morale"--